Behaviour to Use E-Tax Court System: An Approach of Technology Acceptance Model (TAM) - Dara Puspitaningrum; Khomsiyah Khomsiyah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research aims to examine the factors influencing the behavioral intention to use the e-Tax Court system by applying the Technology Acceptance Model (TAM). The study population consists of 1,237 taxpayers who submitted appeals or lawsuits to the Tax Court through the e-Tax Court platform between July 2023 and September 2024. The sample includes 200 e-Tax Court users selected through a systematic random sampling method. Data was collected via questionnaires distributed from October to November 2024, yielding 101 valid responses for analysis using Structural Equation Modeling-Partial Least Square (SEM-PLS). The findings indicate that perceived ease of use and perceived usefulness positively influence attitudes toward using the e-Tax Court system. Additionally, the study reveals that attitudes toward using the e-Tax Court significantly impact the intention to use the platform. However, perceived usefulness does not have a significant effect on the intention to use the e-Tax Court system.